Belajar dalam Genggaman: Studi Pustaka Dampak Gadget terhadap Siswa Sekolah Dasar di Era Digital - Salwa Dwi Rahmayani; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The advancement of digital technology has increased gadget use among elementary school students. This article aims to examine various studies on the impact of gadgets on students’ behavior and learning processes. This paper employs a literature review method by referring to several relevant scholarly sources. The findings indicate that gadgets can support learning such as through information access and educational applications but may also cause negative effects like addiction, concentration issues, and reduced social interaction if used unwisely. The discussion highlights the important roles of teachers and parents in guiding students toward healthy technology use. In conclusion, gadget usage should be accompanied by digital literacy and proper supervision to ensure it truly supports students’ development in the digital era.